An anencephalic monocephalus diprosopus "headed twin": postmortem and CT findings with emphasis on the cranial bones - (:unkn) unknown (My University, 2005)
Monocephalus diprosopus is a form of conjoined twinning characterized by a single body, one unusual head and two faces or a spectrum of duplication of the craniofacial structures. Such cases have been mainly described according to postmortem pathologic examination. This presented case is a 26-week-stillborn female fetus, with unusual facial appearance with four eyes, two mouths, two noses, two ears and a defective cranial vault. To our knowledge, a detailed computerized tomography (CT) examination of the aberrant facial and cranial bones of such a case has not been reported to date. In this reported case, we present an anencephalic monocephalus diprosopus "headed twin", and describe the CT findings with emphasis on the cranial bones.
Keywords: Female; Humans; Pregnancy; Tomography, X-Ray Computed; Face; Skull; Head; Anencephaly; Facial Bones; Petrous Bone; Pregnancy Outcome; Twins, Conjoined